2006
DOI: 10.1007/s00442-006-0527-8
|View full text |Cite
|
Sign up to set email alerts
|

Predators induce egg retention in prey

Abstract: To prevent predation on their eggs, prey often avoid patches occupied by predators. As a result, they need to delay oviposition until they reach predator-free patches. Because many species allocate energy to egg production in a continuous fashion, it is not clear what kind of mechanism prey use to delay oviposition. We used females of the phytoseiid mite Neoseiulus cucumeris to study these mechanisms. Females were placed in patches with pollen, a food source they use for egg production, and they were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 32 publications
1
48
1
4
Order By: Relevance
“…Our second prediction, that predation may create attractive cues, was confirmed by the Predator feeding on prey experiment. This result strongly contrasts with previous reports that diverse organisms avoid ovipositing where predators or their cues are present (Angelon and Petranka 2002; Binckley and Resitarits 2002, 2005, 2008, Orizaola and Braña 2003; Blaustein et al 2004; Arav and Blaustein 2006; Montserrat et al 2007; Silberbush and Blaustein 2008; Silberbush et al 2010). Though some investigations have found no avoidance of oviposition with predators (e.g., Orizaola and Braña 2003, Juliano et al 2010, Hurst et al 2010, reviewed by Vonesh and Blaustein 2010), finding preferential oviposition where predators have been active is a rarity (see Torre-Estrada et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Our second prediction, that predation may create attractive cues, was confirmed by the Predator feeding on prey experiment. This result strongly contrasts with previous reports that diverse organisms avoid ovipositing where predators or their cues are present (Angelon and Petranka 2002; Binckley and Resitarits 2002, 2005, 2008, Orizaola and Braña 2003; Blaustein et al 2004; Arav and Blaustein 2006; Montserrat et al 2007; Silberbush and Blaustein 2008; Silberbush et al 2010). Though some investigations have found no avoidance of oviposition with predators (e.g., Orizaola and Braña 2003, Juliano et al 2010, Hurst et al 2010, reviewed by Vonesh and Blaustein 2010), finding preferential oviposition where predators have been active is a rarity (see Torre-Estrada et al.…”
Section: Discussioncontrasting
confidence: 99%
“…However, there were still a number of spider mite adults and eggs left on the leaf discs at the end of the performance experiment, suggesting that there was no shortage of the superior food source. It is also possible that the presence of thrips larvae induced egg retention in the predators (Faraji et al 2001; Montserrat et al 2007; de Almeida and Janssen 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, a reduction in oviposition may be one antipredator behavior for prey animals. It is reported that some females avoid ovipositing near their predators (Faraji et al 2001;Agarwala et al 2003;Nomikou et al 2003), and retain eggs inside of their body in the presence of predators (Montserrat et al 2007). For example, females of the phytophagous mite Tetranychus urticae have been reported to reduce oviposition in the presence of the predatory mite Phytoseiulus persimilis (Š kaloudová et al 2007), and to increase migration from a patch with predators to avoid predation (Choh and Takabayashi 2007).…”
Section: Introductionmentioning
confidence: 99%